2022
DOI: 10.1038/s41377-022-00905-6
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional resonant wavefront-shaping meta-optics based on multilayer and multi-perturbation nonlocal metasurfaces

Abstract: Photonic devices rarely provide both elaborate spatial control and sharp spectral control over an incoming wavefront. In optical metasurfaces, for example, the localized modes of individual meta-units govern the wavefront shape over a broad bandwidth, while nonlocal lattice modes extended over many unit cells support high quality-factor resonances. Here, we experimentally demonstrate nonlocal dielectric metasurfaces in the near-infrared that offer both spatial and spectral control of light, realizing metalense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 46 publications
1
76
0
Order By: Relevance
“…Copyright 2022 the Authors. (c) Reprinted under the terms of Creative Commons license () from ref . Copyright 2022 the Authors, published by Springer Nature.…”
Section: Novel Optical Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Copyright 2022 the Authors. (c) Reprinted under the terms of Creative Commons license () from ref . Copyright 2022 the Authors, published by Springer Nature.…”
Section: Novel Optical Effectsmentioning
confidence: 99%
“…22 (c) SEM image of multifunctional few-layer metasurfaces exploiting multiperturbations on nonlocal modes. 23 (d) Dynamic focusing by perturbative metagratings composed of photorefractive silicon nanolines. 72 (e) SEM image of superthin high-Q matagratings with independent diffraction efficiency across different wavelength bands.…”
Section: ■ Novel Optical Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…But the corresponding radiation patterns have complicated high order features, making them poor candidates for metasurface building blocks 33,34 . Nonlocal metasurfaces exhibiting high-Q extended modes that have shaped instead of at phase distributions have also emerged [35][36][37] . Rather than applying a tailored transfer function to incoming waves, these structures can resonantly enhance speci c wavefronts, which is useful for focusing incoherent emission 38 , for example.…”
Section: Introductionmentioning
confidence: 99%
“…In recent work published in Light: Science & Applications , Malek et al experimentally demonstrated a multifunctional platform of nonlocal metasurfaces in the near-infrared region for independent multispectral wavefront shaping with high Q-factors 12 . The systems are based on photonic crystal slabs fabricated on an amorphous silicon film etched with pairs of rectangular holes on silica substrate supporting q-BICs encoded with a spatially varying geometric phase.…”
mentioning
confidence: 99%